Covering the European Union - From an Intergovernmental towards a Supranational Perspective? - van Cauwenberge, Anna; Gelders, Dave; Joris, Willem (Javnost-The Public, 2009)
This article investigates the cross-national prevalence of fi ve news frames in quality papers’ coverage of the Treaty of Lisbon (EU Constitution). Three frames were identifi ed in earlier studies: economic consequences, confl ict, and human interest. Two additional frames were identifi ed and composed: power and nationalisation. During the seven-month period leading up to the signing of the Treaty of Lisbon (December 2007), we analysed 341 articles from four quality papers: Le Monde (France), De Volkskrant (The Netherlands), De Standaard (Dutch speaking community of Belgium), and Le Soir (French speaking community of Belgium). Our results show that although signifi cant differences between newspapers were found in the amount of framing, overall they refl ected a similar pattern in the adoption of the news frames. The economic consequences frame, followed by the power frame, appeared most prominently in all of the newspapers’ coverage. However, the confl ict and nationalisation frames recurred in a signifi cantly lesser degree. These fi ndings indicate that the meaning behind the EU Constitution as a symbol of supranational unity could have led to a shift from a domesticated, confl ict oriented coverage as found in previous studies to a more unifi ed portrayal of the EU within and between the quality papers under study.